PENGARUH EARNINGS, CASH FLOW FROM OPERATIONS, WORKING CAPITAL FROM OPERATIONS, DAN ACCRUAL COMPONENTS TERHADAP FUTURE CASH FLOW PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewi, Sofia Prima; Gunawan, Venny (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
The purpose of this study was to obtain empirical evidence about the effect of earnings, cash flow from operations, working capital from operations, and accrual components to future cash flow in manufacturing companies listed in Indonesia Stock Exchange. The samples used were 165 manufacturing companies listed in Indonesia Stock Exchange during 2010-2012. Data analysis was performed with the aid of a software program Statistical Product and Service Solutions (SPSS)for Windows. The results showed that earnings, cash flow from operations, and working capital from operations have an influence on future cash flow, while accrual components does not have any influence on future cash flow.